High‐Temperature Oxidation of ZrB2–SiC–AlN Composites at 1600°C. Issue 3 (21st December 2015) - Ouyang, Gaoyuan; Ray, Pratik K; Kramer, Matthew J; Akinc, Mufit
Abstract : The effect of AlN substitution on oxidation of ZrB2 –SiC was evaluated at 1600°C up to 5 h. Replacement of ZrB2 by AlN, with 30 vol% SiC resulted in improved oxidation resistance with a thinner scale and reduced oxygen affected area. On the other hand, substitution of AlN for SiC resulted in a deterioration of the oxidation resistance with an abnormal scale and significant recession. The effect of SiC content was also studied, and was found to be consistent with the literature for the composites without AlN additions. A similar effect was observed when AlN was added, with the higher SiC content materials showing improved oxidation resistance. X‐ray photoelectron spectroscopy showed the presence of Al2 O3 and SiO2 on the surface, which could possibly lead to a modification in the viscosity of the glassy oxide scale. Possibly, the oxidation behavior of ZrB2 –SiC composites can be improved with controlled AlN additions by adjusting the Al:Si ratios.